Implementasi Peraturan Daerah No 6 Tahun 2019 Tentang Strategi Pembangunan Kepariwisataan Pada Dinas Pariwisata Kabupaten Labuhanbatu Selatan - Fengky Aryo Aritonang; Budi Hartono; Novita Wulandari (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2023)
The Department of Youth, Sports and Tourism of South Labuhanbatu Regency is 2 (two) different offices, namely the Office of Youth and Sports and the Office of Tourism. In 2002, these two agencies merged to become the Youth, Sports and Tourism Office which is expected to further optimize and synergize in carrying out development in the field of youth sports and tourism objects in South Labuhanbatu Regency. In this case, the Tourism and Culture Office of South Labuhanbatu Regency as the implementer of the regional regulation policy No. 6 of 2019 Chapter VI Concerning Tourism Development Strategies in Simalungun Regency. The theory used in this research is Implementation theory by Edward III, this research uses a qualitative type methodology which using interview techniques, observation, and also documentation. As reinforcement, this study also consisted of key informants, main informants and additional informants using data analysis techniques by Miles and Huberman namely data collection, data reduction, data presentation and conclusions.